Evaluation of the Efficacy of Topical Tacrolimus and Intraperitoneal Cyclosporine as a Treatment Method for Acute Rejection In vivo Model of Skin Allotransplantation - Dilgam Mammadov; Kamuran Zeynep Sevim Aytuğ; Nedim Polat (Turkish Journal of Plastic Surgery)
Aims: Skin allotransplantation often results in graft rejection, necessitating the use of immunosuppressants. Tacrolimus (Tac) and cyclosporine A (CsA) are two commonly used immunosuppressants in this context. However, the efficacies of both agents in various formulations remain unclear. In this regard, this study was conducted to evaluate the efficacies of using topical Tac and intraperitoneal CsA, stand-alone and in combination, in preventing acute rejection following rat skin allotransplantation. Setting and Design: This study was designed as a double-blind experimental animal study. It was conducted under veterinary control in accordance with EU Directive 2010/63/EU for animal experiments and national regulations at the Animal Experimentation Research Laboratory of Bezmialem Foundation University in Turkey. Materials and Methods: The study material consisted of 20 female albino Wistar (WIS) rats that underwent skin allograft transplantation. These rats were randomly divided into four groups according to the treatment they were administered: the Tac group, the CsA group, the Tac and CsA group, and the control group. Rejection symptoms were monitored over a month, followed by macroscopic and histopathological evaluations of the grafts. Statistical Analysis Used: Qualitative data were analysed using the Chi-square test, and in cases where Chi-square analysis was not appropriate, Fisher’s exact test was used. The efficacies of the treatment drugs were compared between treatment groups using a nonparametric analysis of variance test followed by Dunn’s post hoc test. Results: The most severe (Grade 4) symptoms associated with rejection, both in terms of clinical and histopathological scale scores (P < 0.001), were observed in the control group. The mildest rejection-associated symptoms, i.e. mainly (80%) Grade 0 symptoms, were observed in the Tac group, followed by the Tac and CsA group, where Grade 0, 1, and 2 symptoms were observed in 60%, 20%, and 20% of the rats, respectively, and the CsA group, where Grade 1, 2, and 3 symptoms were observed in 20%, 40%, and 40% of the rats, respectively. Conclusions: Stand-alone topical Tac was found to be more effective in mitigating acute rejection than stand-alone CsA and Tac and CsA in combination, suggesting its potential as a superior treatment modality in skin allotransplantation.